Molecular treatments to reduce catabolic effects in human meniscus explant models - Amanda Sjögren; Karin Lindblom; Aleksandra Turkiewicz; Martin Englund; Patrik Önnerfjord (Osteoarthritis and Cartilage Open)
Objectives: 1. To validate catabolic meniscus explant models induced by cytokines: interleukin-6 ​+ ​interleukin-6 receptor ​+ ​tumor necrosis factor alpha (IL6/TNF) and oncostatin M ​+ ​tumor necrosis factor alpha (OSM/TNF). 2. To evaluate three potential anti-catabolic treatments: i) dexamethasone (DEX), ii) a Link-N peptide (Link-N) and iii) a peptide from chondroadherin (CKF). Design: Healthy lateral menisci from deceased donors (n ​= ​6; age ​= ​25–70 years, 4 males, 2 females), were sliced and randomized for experimental groups (combinations of the catabolic models and anti-catabolic treatments) and a control group. Culture media were analyzed, every third day until day 18, by mass spectrometry-based proteomics. Linear mixed effect models were used to estimate differences in protein abundances between groups. Results: A total of 662 proteins were identified in all menisci. Cytokine-treated meniscus explant models showed increased release of osteoarthritis-related proteins such as matrix metalloproteinases (MMPs). For example, MMP1: IL6/TNF vs. ctrl; log2 fold-change 2.2 95 ​% confidence interval [1.8, 2.5] and OSM/TNF vs. ctrl; log2 fold-change 2.8 [2.4, 3.1]. There was no treatment effect in explant meniscus with the addition of either Link-N or CKF. Treatment effects were, however, evident with the addition of DEX. For example, MMP1: IL6/TNF ​+ ​DEX vs. ctrl; log2 fold-change −1.8 [-2.2, −1.4] and OSM/TNF ​+ ​DEX vs. ctrl; log2 fold-change −0.3 [-0.7, 0.04]. Conclusion: We confirmed that both catabolic models induce changes in osteoarthritis-related proteins. DEX treatment is effective in mitigating the catabolic response in meniscus explant models and may be further explored for its effects in the treatment of meniscus degeneration.